Household debt and monetary policy: Revealing the cash-flow channel - Martin Flodén; Matilda Kilström; Jósef Sigurdsson; Roine Vestman (Sveriges Riksbank, 2017)
We examine the cash-flow channel of monetary policy, i.e. the effect of monetary policy on spending when households hold debt linked to short-term rates such as adjustable rate mortgages (ARMs). Using registry-based data on Swedish households, we estimate substantial heterogeneity in consumption responses to a change in monetary policy through the cash-flow channel. Our findings imply that monetary policy has a stronger effect on real economic activity when households are highly indebted and have ARMs. For homeowners with a debt-to-income ratio of around 3 and ARMs, the estimated response is equivalent to a marginal propensity to consume of 0.5.
Keywords: D14; E21; E52; G11; 330; Monetary policy; consumption; household debt; variable interest rates; adjustable rate mortgages